PREPARATION AND CHARACTERIZATION OF ACTIVATED CARBON FROM DATE PALM (Phoenix dactylifera) SEEDS (FUDMA JOURNAL OF SCIENCES, 2024)
In this study, agricultural waste (date seeds) were used to produce activated carbon in an oxygenated environment. The produced activated carbon was characterised. The HRSEM showed mesoporous structural morphology, which exhibited a surface area of 54.53 m2/g, pore size of 10.34 nm and pore volume of 0.1256 cc/g. The EDX spectrum revealed the presence of C and O as the major elemental compositions in the activated carbon. The FTIR spectrum indicated the presence of OH-, C=C, C=O and C-H at absorption bands of 3400, 2900, 1650, and 1300 cm-1, respectively.  The diffractogram of the activated carbon revealed graphitic carbon 2 peaks of 22o and 43o which are related to (002) and (100) plane, respectively. The conversion of agricultural waste to activated carbon possessing these unique properties could serve as a promising and low-cost adsorbent for the removal of toxic pollutants from industrial wastewater.
Keywords: Carbonised; Surface area; Low-cost; Adsorbent